KOLEKSI REFERENSI NYAMUK DI DESA JEPANGREJO, KECAMATAN BLORA, KABUPATEN BLORA - Dewi Marbawati; Zumrotus Sholichah (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2009)
Some kind of mosquitoes can transmit desease through their biting. Some of them are Anopheles that transmit malaria, Aedes aegypti and Aedes albopictus transmit Dengue Haemorrhagic Fever (DHF) and chikungunya, some of mosquitoes from Culex, Aedes, Anopheles and Mansonia genera that transmit filaria, etc. To study the mosquitoes diversity , the collection of mosquitoes in different species was needed.In order to increased the mosquitoes collection in LokaLitbang P2B2 Banjarnegara, collection in endemic area were conducted. One of selected area as the location of mosquitoes collection was Blora districtThis survey was observational. Samples were taken with purposive sampling method that was all mosquitoes found during the study. Secondary data collected from health officer and public health center (puskesmas), observing the environment and social activities and also entomological survey. Result of entomological survey were various kind of mosquitoes, in Central Java Province, Blora district i.e.: Culex quinquefasciatus, Culex vishnui, Aedes aegypti, Anopheles vagus and Anopheles indefinitus.